Ethnicity, Race and Inequality in the UK State of the Nation - Byrne, Bridget; Alexander, Claire; Khan, Omar; Nazroo, James; Shankley, William (2020)
Available Open Access under CC-BY-NC licence. 50 years after the establishment of the Runnymede Trust and the Race Relations Act of 1968 which sought to end discrimination in public life, this accessible book provides commentary by some of the UK's foremost scholars of race and ethnicity on data relating to a wide range of sectors of society, including employment, health, education, criminal justice, housing and representation in the arts and media.